Prevalence of depression and anxiety in patients with chronic digestive system diseases: A multicenter epidemiological study - Zhang, An-Zhong; Wang, Qing-Cai; Huang, Kun-Ming; Huang, Jia-Guo; Zhou, Chang-Hong; Sun, Fu-Qiang; Wang, Su-Wen; Wu, Feng-Ting (World journal of gastroenterology : WJG, 2016)
AIM To investigate the prevalence of depression and anxiety in patients with chronic digestive system diseases.METHODS A total of 1736 patients with chronic digestive systemdiseases were included in this cross-sectional study, including 871 outpatients and 865 in-patients. A selfdesigned General Information for Patients of the Department of Gastroenterology of General Hospitals questionnaire was used to collect each patient’s general information, which included demographic data(including age, sex, marital status, and education) and disease characteristics(including major diseases, disease duration, principal symptoms, chronic pain, sleep disorder, and limited daily activities).RESULTS The overall detection rate was 31.11%(540/1736) for depression symptoms alone, 27.02%(469/1736) for anxiety symptoms alone, 20.68%(359/1736) for both depression and anxiety symptoms, and 37.44%(650/1736) for either depression or anxiety symptoms. Subjects aged 70 years or above had the highest detection rate of depression(44.06%) and anxiety symptoms(33.33%). χ2 trend test showed: the higher the body mass index(BMI), the lower the detection rate of depression and anxiety symptoms(χ2trend = 13.697, P < 0.001; χ2trend = 9.082, P = 0.003); the more severe the limited daily activities, the higher the detection rate of depression and anxiety symptoms(χ2trend = 130.455, P < 0.001, χ2trend = 108.528, P < 0.001); and the poorer the sleep quality, the higher the detection rate of depression and anxiety symptoms(χ2trend = 85.759, P < 0.001; χ2trend = 51.969, P < 0.001). Patients with digestive system tumors had the highest detection rate of depression(57.55%) and anxiety(55.19%), followed by patients with liver cirrhosis(41.35% and 48.08%). Depression and anxiety symptoms were also high in subjects with comorbid hypertension and coronary heart disease. CONCLUSION Depression and anxiety occur in patients with tumors, liver cirrhosis, functional dyspepsia, and chronic viral hepatitis. Elderly, divorced/widowed, poor sleep quality, and lower BMI are associated with higher risk of depression and anxiety.